2023
DOI: 10.1177/14777606231218354
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, morphological, and dimensional properties of heat-treated fused deposition modeling printed polymeric matrix of polyethylene terephthalate glycol

Sudhir Kumar,
Inderjeet Singh,
Dinesh Kumar
et al.

Abstract: This study investigates the impact of heat treatment on the mechanical, morphological, and dimensional properties of polyethylene terephthalate glycol (PETG), a commonly used thermoplastic in 3D printing. Taguchi L25 orthogonal array (OA) was employed to optimize 3D printing parameters, considering factors such as infill percentage (ranging from 20% to 100%), layer height (0.12 mm to 0.28 mm), layer width (0.32 mm to 0.62 mm), and infill pattern. Following ASTM D638 type IV standards, mechanical testing reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A new factor, the "Krenchel coefficient (n 0 )," is introduced, which takes into account the fiber orientation angle. The elastic modulus of the composite is calculated through equation (10).…”
Section: Analytical Prediction Of the Mechanical Properties Of 3d-pri...mentioning
confidence: 99%
See 1 more Smart Citation
“…A new factor, the "Krenchel coefficient (n 0 )," is introduced, which takes into account the fiber orientation angle. The elastic modulus of the composite is calculated through equation (10).…”
Section: Analytical Prediction Of the Mechanical Properties Of 3d-pri...mentioning
confidence: 99%
“…Applying a heat treatment to the printed parts can improve the mechanical properties of these thermoplastics. 10 Additionally, the mechanical performance of parts can be enhanced by adding short or long fibers or particles (powder). In a study, Kumar et al 11 demonstrated that the inclusion of wood or iron oxide powder can enhance specific mechanical properties, such as toughness, during recycling cycles.…”
Section: Introductionmentioning
confidence: 99%